2005
DOI: 10.1099/vir.0.80493-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the RNA-binding domain on the Apple chlorotic leaf spot virus movement protein

Abstract: The RNA-binding properties of the cell-to-cell movement protein (MP) of Apple chlorotic leaf spot virus were analysed. MP was expressed in Escherichia coli and was used in UV-crosslinking analysis, using a digoxigenin-UTP-labelled RNA probe and gel-retardation analysis. The analyses demonstrated that MP bound cooperatively to single-stranded RNA (ssRNA). When analysed for NaCl dependence of the RNA-binding activity, the majority of the MP could bind ssRNA even in binding buffer with 1 M NaCl. Furthermore, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…The absence of any intermediate retarded bands indicated that CMV MP bound in a cooperative manner to CMV RNA3, which is consistent with the results reported by Li and Palukaitis (1996). The retarded probes barely entered the gel, and this may be due to a highly cooperative binding between MP and the labeled probe (Nurkiyanova et al, 2001;Isogai and Yoshikawa, 2005). A competition binding assay with unlabeled CMV RNA3 competitor further confirmed that the purified CMV MP was able to bind vRNA in vitro (see Supplemental Figure 2A online).…”
Section: Mp Inhibits Actin Polymerization and Severs Actin Filamesupporting
confidence: 86%
“…The absence of any intermediate retarded bands indicated that CMV MP bound in a cooperative manner to CMV RNA3, which is consistent with the results reported by Li and Palukaitis (1996). The retarded probes barely entered the gel, and this may be due to a highly cooperative binding between MP and the labeled probe (Nurkiyanova et al, 2001;Isogai and Yoshikawa, 2005). A competition binding assay with unlabeled CMV RNA3 competitor further confirmed that the purified CMV MP was able to bind vRNA in vitro (see Supplemental Figure 2A online).…”
Section: Mp Inhibits Actin Polymerization and Severs Actin Filamesupporting
confidence: 86%
“…The N-terminal arginine-rich motif of P20 potentiates these activities as well as intracellular targeting (Palani et al , 2006). In this regard, P20 shares common biological properties with other viral MPs (Carvalho & Lazarowitz, 2004; Hsu et al , 2004; Isogai & Yoshikawa, 2005). In BaMV and satBaMV co-infected N. benthamiana leaves, accumulation of P20 and a serologically related polypeptide of a low molecular mass of 16 kDa (P16) has been detected (Palani et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After the first report of TMV MP binding to nucleic acids, the binding of other MPs to nucleic acids has been reported for 26 other viruses, including (+)RNA viruses, (-) RNA viruses, and DNA viruses (reviewed by Waigmann et al, 2004). In the past decade, at least nine MPs have been added to the list of nucleic acid-binding MPs: Cowpea mosaic virus (CPMV; Carvalho et al, 2004); Prunus necrotic ringspot virus (PNRSV; Herranz and Pallás, 2004); Rice yellow stunt virus (Huang et al, 2005); Apple chlorotic leaf spot virus (Isogai and Yoshikawa, 2005); Rice dwarf virus (Ji et al, 2011); Parietaria mottle virus (Martínez et al, 2014); Pelargonium flower break virus (Martínez-Turiño and Hernández, 2011); Melon necrotic spot virus (Navarro et al, 2006); Rice stripe virus (Xiong et al, 2008). Most MPs can bind single-stranded nucleic acids, and only three viral MPs (one geminivirus and two hordeiviruses) have been shown to bind double-stranded nucleic acids (Bleykasten et al, 1996; Donald et al, 1997; Rojas et al, 1998).…”
Section: Viral Rbps Involved In the Intercellular Movement Of Vrnasmentioning
confidence: 99%